Enhancing antioxidant activity of rice protein hydrolysates through glycosylation modification - Zhang, Zhimin; Bi, Xinjian; Hu, Liangjie; Wu, Ying; Hu, Wenting; Wang, Han; Zheng, Xinyue; Wu, Hao; Mu, Daichen; Wen, Li; Huang, Qingming (Frontiers in Nutrition, 2025)
ObjectiveThis work sought to improve the potential use of rice protein by examining the antioxidant activity of glycosylated rice protein hydrolysates (RPH).MethodsRPH were produced via the enzymatic breakdown of rice protein powder utilizing trypsin. Then, using the Maillard reaction, these hydrolysates were glycosylated with three functional monosaccharides to create RPH-fructose (RPH-F), RPH-xylose (RPH-X), and RPH-arabinose (RPH-A). The antioxidant capabilities of glycosylated derivatives were assessed in vitro by measuring Fe2+ chelating ability and their ability to neutralize several radicals, including hydroxyl (•OH), superoxide anion (O2•−), 2,2-diphenyl-1-picrylhydrazyl radical (DPPH•), and 2,2′-azinobis (3-ethylbenzothiazoline-6-sulfonate) radical (ABTS•+). A zebrafish in vivo model was utilized to investigate oxidative damage, analyzing the distribution of reactive oxygen species (ROS) through fluorescence staining and evaluating oxidative stress by quantifying malondialdehyde (MDA) levels and the activity of antioxidant enzymes such as catalase (CAT) and total superoxide dismutase (T-SOD). Following glycosylation, DPPH• clearance by RPH-X increased by 12.75% (6 mg/mL), and ROS inhibition by RPH-A in the zebrafish model reached 84.78%.ConclusionGlycosylation enhanced the antioxidant capabilities of rice protein hydrolysate, indicating its potential as a functional dietary component with antioxidant efficacy.